Erosi dari Rentang Perhatian Menjadi Hiburan Digital Berlebih - Aulia Putri Junitasari; Angellina Putri Febriyanti; Jihan Sahilina Shofa; Sri Isnani Setyaningsih (Puslitbang Akademi Relawan TIK Indonesia, 2026)
The phenomenon of brain rot has attracted increasing attention alongside the growing consumption of short-form digital content, particularly among Generation Z and Generation Alpha. Although numerous studies have examined the effects of gadget and social media use on concentration, research that comprehensively explores brain rot from neurological, psychological, and educational perspectives remains limited. Therefore, this article aims to examine the mechanisms underlying the development of brain rot, analyze its impact on attention span and executive function, and identify its implications for social and educational life. This study employs a literature review method using a descriptive qualitative approach. The data were collected from articles indexed in Google Scholar and Crossref published between 2020 and 2025. Of the 187 articles identified during the initial search, 32 articles were selected for further analysis based on predetermined inclusion and exclusion criteria. The findings indicate that exposure to fast-paced, repetitive, and low-depth digital content can foster a tendency toward instant gratification through the activation of the dopamine reward system. This condition contributes to reduced attention span, weakened executive function, diminished critical thinking skills, and an increased tendency to become easily distracted. Furthermore, the impacts of brain rot extend beyond cognitive aspects, affecting psychological well-being through increased anxiety and fear of missing out (FOMO), social aspects through declining interpersonal interaction quality, and educational aspects through reduced capacity for deep and sustained learning. The novelty of this article lies in its integration of findings from neuroscience, psychology, and education to explain the relationship between instant digital content consumption and changes in cognitive abilities and individual behavior. These findings highlight the importance of strengthening digital literacy, regulating gadget use, and promoting support from families and educational institutions to encourage healthier and more balanced digital habits.